Performance assessment of walls using the Analytic Hierarchy Process in decision-making - Caldas, Lucas Rosse (Universidade Estadual de Campinas, 2018)
The performance assessment of construction systems has been a subject widely discussed in the Brazilian building sector. This paper aimed to evaluate the acoustic, thermal and environmental performance of different constructive systems typically used in façades of residential buildings. We assessed the following construction systems: ceramic block masonry, ceramic brick masonry, concrete block structural masonry, reinforced concrete wall and steel framing. For the acoustic performance, the weighted noise reduction index (Rw) was calculated, while for the thermal performance of the thermal resistance (Rt) and the thermal capacity (Ct) were calculated. For the environmental performance assessment, two indicators were quantified: a fossil fuels energy consumption index (IE) and a carbon index (IC), based on the Life Cycle Assessment (LCA) methodology. As a way to facilitate the decision-making process of designers, we used the Analytic Hierarchy Process (AHP) to aggregate the different criteria to a global performance index (GDI).  When the GDI is calculated, the concrete block masonry system presented the best results for most of the evaluated scenarios.  We verified the potential of using the AHP method to guide and systematize the choice of different constructive systems for walls.